Service quality, customer satisfaction, and customer loyalty - Muhammad Hanif; Susi Evanita (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of service quality on customer satisfaction and loyalty of Regional Drinking Water Company (PDAM) in Lima Puluh Kota Regency. This type of research is descriptive research with a quantitative approach. The research population is all PDAM in Lima Puluh Kota whose house connection accounts are still active, with as many as 13,178 customers. Determination of respondents using probability sampling that is systematic random sampling totaling 100 people. This study used an online questionnaire as a data collection instrument and analyzed using the SPSS version 25 program. The results showed that: (1) service quality was proven to have a significant effect on customer satisfaction, (2) customer satisfaction was proven to significantly affect customer loyalty, (3) customer satisfaction is proven to mediate the effect of service quality on customer loyalty at PDAM in Lima Puluh Kota Regency.